Scripting Stranger Sexual Offenses Against Women. (March 2021) - Chiu, Yi-Ning; Leclerc, Benoit
This study identifies the first crime script for unsolved stranger sexual offenses against women. The purpose is to better understand the crime-commission process of solved and unsolved stranger sexual offenses and identify potential points of intervention for prevention purposes. Crime script analysis was performed on 542 solved ( n = 265) and unsolved ( n = 277) cases based on police data in Queensland, Australia, followed by a comparison between solved and unsolved crime scripts. Results showed that unsolved offenses tended to be associated with the following factors: the offender fleeing/desisting, using minimal force, less intrusive sexual outcomes, and less verbal engagement with the victim. In these cases, there was a lack of information regarding forensic evidence, behavioral clues, and eyewitness leads. This highlights the relevance of focusing on situational crime prevention and policing strategies that may deter stranger sexual crimes at the earliest stages of the script.